PENYULUHAN BAHAYA KEBAKARAN DAN UPAYA PENYELAMATAN BAGI ANAK DAN REMAJA DI JEMAAT GPI. PAPUA BETHLEHEM KOTA SORONG - Febry Talakua (Politeknik Negeri Sriwijaya, 2022)
Fires that occur will have an impact on the community, namely causing losses to both property owned and human souls. Fire is a disaster that threatens and is very scary for everyone. The extension is the process of conveying information to others by an extension worker. Counseling on the dangers of fire and rescue efforts is given to the GPI congregation of children and youth (PAR). Papua Berthlehem Sorong city. This activity aims to increase knowledge and provide behavior change for children and adolescents about the dangers of fire. The method used in counseling is educating through lectures, discussions, and questions and answers as well as the presentation of material in the form of power points. The results showed that from the results of the posttest and pretest tests, the average knowledge values ​​were 4.2 and 8.1. After being given counseling, there is an increase in knowledge with a difference of 3.9. This activity concludes that there is an increase in knowledge that is getting better and changes in behavior in children and adolescents after counseling and education about the dangers of fire and rescue efforts are carried out. For this reason, we hope that in the future the government, Non-Governmental Organizations (NGOs), and Religious Institutions can increase collaboration with universities in community service activities regarding fire hazard education and rescue efforts for children and adolescents.